Analisis Minat Siswa SMP terhadap Ekstrakurikuler PMR dan Urgensinya Menumbuhkan Jiwa Sosial - Anggun Puspita Sari; Kasan Bisri (Pendekar: Jurnal Pendidikan Berkarakter, 2025)
Abstract: The Youth Red Cross (PMR) extracurricular activity at SMPN 16 Semarang is one of the most popular activities for students. The high participation indicates a strong tendency for students to engage in social activities from an early age. However, despite PMR's great potential in fostering social character, there is still limited understanding of students' initial motivations, the impact of their involvement, and challenges in its implementation. This study aims to analyze the interest, motivation, social impact, constraints, and development strategies of PMR activities. The approach used was sequential exploratory mixed methods, where qualitative data from interviews and observations were analyzed first to form a questionnaire instrument which was then studied quantitatively. The results showed that the dominant motivation for students to join PMR was the desire to learn first aid and gain social experience. PMR activities are proven to contribute to fostering empathy and social care through student involvement in humanitarian action. However, this activity still faces obstacles such as fluctuations in attendance, lack of facilities, and uneven participation. Strengthening strategies are carried out through schedule adjustments, variations in training methods, and expansion of external cooperation. This research makes a real contribution to the development of extracurricular activities based on social character, and can be a reference for school managers in designing adaptive and sustainable programs.Abstrak: Ekstrakurikuler Palang Merah Remaja (PMR) di SMPN 16 Semarang merupakan salah satu kegiatan yang paling diminati oleh siswa. Tingginya partisipasi menunjukkan adanya kecenderungan kuat siswa untuk terlibat dalam aktivitas sosial sejak dini. Namun, meskipun PMR berpotensi besar dalam menumbuhkan karakter sosial, masih terdapat keterbatasan pemahaman terkait motivasi awal siswa, dampak keterlibatan mereka, serta tantangan dalam pelaksanaannya. Penelitian ini bertujuan untuk menganalisis minat, motivasi, dampak sosial, kendala, dan strategi pengembangan kegiatan PMR. Pendekatan yang digunakan adalah mixed methods eksploratori sekuensial, di mana data kualitatif dari wawancara dan observasi dianalisis terlebih dahulu untuk membentuk instrumen angket yang kemudian dikaji secara kuantitatif. Hasil penelitian menunjukkan bahwa motivasi dominan siswa bergabung dalam PMR adalah keinginan belajar pertolongan pertama dan memperoleh pengalaman sosial. Kegiatan PMR terbukti berkontribusi dalam menumbuhkan empati dan kepedulian sosial melalui keterlibatan siswa dalam aksi kemanusiaan. Namun, kegiatan ini masih menghadapi kendala seperti fluktuasi kehadiran, minimnya fasilitas, dan partisipasi yang belum merata. Strategi penguatan dilakukan melalui penyesuaian jadwal, variasi metode pelatihan, serta perluasan kerja sama eksternal. Penelitian ini memberikan kontribusi nyata dalam pengembangan kegiatan ekstrakurikuler berbasis karakter sosial, dan dapat menjadi acuan bagi pengelola sekolah dalam merancang program yang adaptif dan berkelanjutan.